Polityka onomastyczna władz jako element przywracania polskości na Ziemiach Zachodnich po II wojnie światowej (na przykładzie nazewnictwa powiatu słubickiego) = The onomastic policy of the government as the element of restoring the Polish identity in the Western Recovered Lands after World War II (using the example of the nomenclature in the Słubice County) - Utracki, Damian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the issues related to the post-war onomastic problems on the so-called "Recovered Lands". This issue is important because it depicts the essence of social, political and administrative changes that occurred after World War II in these lands. The main aim was to show the complexity of the problems stemming from re-introducing local names. It was also important to depict the significance of the Polish identity of those names for the newly resettled population.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia